Table olive flours: an ingredient rich in bioactive compounds? - Rodrigues, Nuno (2022)
The aim of this study was to produce different “table olive flours” from fruits at different maturation stages. “Table olive flour” is here presented as an innovative product that can gain importance as a bioactive rich ingredient. Three types of natural table olives from cv. Cobrançosa, i.e., green, turning color, and black olives, were soaked, freeze-dried and ground to obtain three different flours. Their physical and nutritional characterization, lipid fraction (fatty acids and tocopherols profiles), phenolic profile, and antioxidant activity (total reducing capacity, radical scavenging activities of DPPH and ABTS +) were analyzed. “Table olive flours” with different colors and different characteristics were obtained. The “green table olive flour” had the lowest fat content and energy. On the contrary, it showed the highest protein, carbohydrate contents, percentages of oleic acid (C18:1), and MUFA, as well as total tocopherols. It also showed the highest antioxidant activity. The “black table olive flour” was the one with the highest percentages of palmitic acid (C16:0), SFA, and total reducing capacity. In the three types of developed “flours”, nine phenolic compounds were detected, hydroxy-tyrosol being the major, followed by tyrosol, and luteolin. In conclusion, from natural table olives of cv. Cobrançosa, different “table olive flours” with distinct properties and high amounts of health-promoting compounds can be produced.